Concurrent and Concordant Oral and Genital High-Risk Human Papillomavirus in the United States: Results from the National Health and Nutrition Examination Survey. (17th August 2020) - Custer, James; Patel, Riddhi; Delclos, George L; DeSantis, Stacia M
Abstract: Background: Oropharyngeal cancers associated with high-risk human papillomavirus (HR-HPV) infection are increasing in the United States, especially among men. We evaluated the prevalence and predictors of concurrent (genital and oral) and concordant (same-type) HR-HPV infections in the United States. Methods: We used the National Health and Nutrition Examination Survey from 2009 to 2016. Predictors were assessed via multivariable logistic regression. Results: Among 10 334 respondents, 172 (2.1%) had concurrent infections (109 [3.5%] men and 63 [0.76%] women]. Ninety-three (1.0%) had concordant infections (54 [1.6%] men and 39 [0.5%] women). Predictors of concurrence in men included the following: no longer married versus married (odds ratio [OR], 2.3; 95% confidence interval [CI], 1.3–4.9), living with a partner versus married (3.0; 1.2–7.5), and having 2–5 lifetime oral sex partners (3.0; 1.2–7.5). In women they included the following: no longer married versus married (3.6; 1.3–10.3), ≥2 recent sex partners (4.6; 1.4–15.6 for 2–5 partners and 3.9; 1.1–14.3 for ≥6 partners), and marijuana use (2.2; 1.0–4.5). The predictor of concordance in men and women was no longer married versus married (3.5; 1.2–9.9 in men and 3.2; 1.1–9.4 in women). Conclusions: Concurrent and concordant HR-HPV infections occur at a high rate, especially among men, and are associated with behavioral factors. This underscores the importance of HPV vaccination, screening, and education in men. Abstract : This study found a high prevalence rates of concurrent and concordant high-risk human papillomavirus (HR-HPV) infections, especially among men, adding to the knowledge base for developing new screening and vaccination guidelines for HR-HPV infections, specifically targeting the US male population.